Impact of coastal currents and eddies on particle dispersion in the Baltic Sea: a Lagrangian approach to marine ecosystems - Hariri, Saeed; Väli, Germo; Meier, H. E. Markus (Frontiers in Marine Science, 2025)
This study analyzes the dynamics of coastal currents and eddies in the Baltic Sea, focusing on their role in particle dispersion and ecosystem connectivity. Combining the General Estuarine Transport Model (GETM) and Lagrangian methods, it examines both single and paired particle dynamics, initially deployed in coastal areas of the Baltic Sea, for 2D and 3D simulations. Results show significant variability in transit times as it takes for 3D particles from the eastern coastal zone over 700 days to reach the central Gotland Basin, while those from the western coastal zone arrive 90 days faster. Longer transit times in the eastern coastal areas can influence the distribution of nutrients and pollutants, potentially exacerbating eutrophication, harmful algal blooms, and hypoxic conditions. In contrast, shorter transit times in the western Baltic accelerate dispersal, reducing localized impacts while increasing the spread of contaminants. In addition, (sub-)mesoscale eddies and vertical advection play a key role in particle transport, particularly in the northern Gotland Basin, where complex circulation slows movement and prolongs exposure to nutrients and pollutants. Moreover, relative dispersion analysis shows an initial nonlocal growth regime lasting up to 25 days in 3D but only 4–10 days in 2D, affecting connectivity between marine habitats. The subsequent ballistic regime, lasting 350 days in 2D but only 75 days in 3D, suggests enhanced mixing in 3D, influencing species recruitment and the dispersion of pollutants. 3D simulation results show that, depending on the region, absolute dispersion exhibits ballistic growth for the first 7 days, followed by a transition to a super-diffusion regime before normal diffusion sets in after 70–85 days. Furthermore, particle exit times vary also significantly, with those from the Gulf of Finland taking over 1,300 days to exit the Baltic Sea, compared to less than 700 days for particles from western regions. These findings highlight the role of physical processes such as eddies, coastal currents and mesoscale structures in shaping species dispersal, nutrient cycling, and pollution transport. Understanding these mechanisms is crucial for marine conservation, sustainable fisheries, and climate adaptation strategies in coastal marine protected areas (MPAs) of the Baltic Sea, particularly as circulation patterns evolve due to climate change.